Penggunaan Klausa Nomina dalam Website Berita JawaPos Edisi Agustus 2025 - Nayla Zelda Khairunisa; Nabila Khairunnisa Alyamanda; Farah Ilma Jauhara; Annisa Prima Lia Nanda; Chandra Hadi Cipto Nugroho; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Arum Yuliya Lestari (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This study aims to describe the structure, syntactic function, and semantic role of the nominal clause in JawaPos.com news texts published in August 2025. By using a descriptive qualitative approach, this study applied syntactic analysis to explore how the nominal clause operates within the linguistic and contextual framework of media discourse. Data were collected from online news articles and analyzed using Indonesian syntactic and semantic theory. The results show that nominal clauses play a crucial role in constructing discourse structure and meaning through their syntactic functions as subjects, objects, complements, and adverbs. In semantics, nominal clauses perform various roles, including as agents, objects, recipients, and markers of condition or location. The pattern of nominal clause use reflects the concise, efficient, and communicative nature of journalistic language. The correlation between syntactic function and semantic role shows a cohesive relationship that enhances clarity and accuracy in conveying information. This study contributes to the development of syntactic and media linguistic research and serves as a valuable reference for journalists and language educators in promoting effective and ethical language use in journalism.